Studies on bacterial community composition are affected by the time and storage method of the rumen content (2017)
The objective of this study was to investigate three storage methods and four storage times for rumen sampling in terms of quality and yield of extracted metagenomic DNA as well as the composition of the rumen bacterial community. One Nellore steer fitted with a ruminal silicone- type cannula was used as a donor of ruminal contents. The experiment comprised 11 experimental groups: pellet control (PC), lyophilized control (LC), P-20: pellet stored frozen at -20ÊC for a period of 3, 6, and 12 months, P-80: pellet stored frozen at -80ÊC for a period of 3, 6, and 12 months, and L-20: lyophilized sample stored frozen at -20ÊC for a period of 3, 6, and 12 months. Metagenomic DNA concentrations were measured spectrophotometrically and fluorometrically and ion torrent sequencing was used to assess the bacterial community composition. The L-20 method could not maintain the yield of DNA during storage. In addition, the P-80 group showed a greater yield of metagenomic DNA than the other groups after 6 months of storage. Rumen samples stored as pellets (P-20 and P-80) resulted in lower richness Chao 1, ACE, and Shannon Wiener indices when compared to PC, while LC and PC were only different in richness ACE. The storage method and storage time influenced the proportions of 14 of 17 phyla identified by sequencing. In the P-20 group, the proportion of Cyanobacteria, Elusimicrobia, Fibrobacteres, Lentisphaerae, Proteobacteria, and Spirochaetes phyla identified was lower than 1%. In the P-80 group, there was an increase in the proportion of the Bacteroidetes phylum (p = 0.010); however, the proportion of Actinobacteria, Chloroflexi, SR1, Synergistetes, TM7, and WPS.2 phyla were unchanged compared to the PC group (p > 0.05). The class Clostridium was the most abundant in all stored groups and increased in its proportion, especially in the L-20 group. The rumen sample storage time significantly reduced the yield of metagenomic DNA extracted. Therefore, the storage method can influence the abundance of phyla, classes, and bacterial families studied in rumen samples and affect the richness and diversity index.